Exploring the Theological Context to Domestic and Family Violence - Clarke, Josephine (Violence against women, 2025)
This article explores the theological drivers of domestic and family violence (DFV)—specifically intimate partner violence—by engaging with ecclesiastical beliefs and practices of the Lutheran Church of Australia (LCA). Key theological, policy, and public documents were analyzed to understand gender relations, gender roles, marriage, ordination, ethical behavior, and responses to DFV. Findings from the document analysis demonstrate church practice and policy reforms underway in addressing violence against women and supporting safety. Simultaneously, the documents show contested and troubled positions regarding gender relations, the theological context to gender roles and responsibilities and the church's journey of debating (re)configuration of its organizational structure and responsibilities.